Association Mapping of Flowering and Height Traits in Germplasm Enhancement of Maize Doubled Haploid (GEM‐DH) Lines. Issue 2 (1st July 2018) - Vanous, Adam; Gardner, Candice; Blanco, Michael; Martin‐Schwarze, Adam; Lipka, Alexander E.; Flint‐Garcia, Sherry; Bohn, Martin; Edwards, Jode; Lübberstedt, Thomas
Abstract : Flowering and height related traits are extensively studied in maize for three main reasons: 1) easily obtained phenotypic measurements, 2) highly heritable, and 3) importance of these traits to adaptation and grain yield. However, variation in flowering and height traits is extensive and findings from previous studies are genotype specific. Herein, a diverse panel of exotic derived doubled haploid lines, in conjunction with genome‐wide association analysis, is used to further explore adaptation related trait variation of exotic germplasm for potential use in adapting exotic germplasm to the U.S. Corn‐Belt. Phenotypes for the association panel were obtained from six locations across the central‐U.S. and genotyping was performed using the genotyping‐by‐sequencing method. Nineteen flowering time candidate genes were found for three flowering traits. Eighteen candidate genes were found for four height related traits, with the majority of the candidate genes relating to plant hormones auxin and gibberellin. A single gene was discovered for ear height that also had effects on FT ‐like flowering gene expression levels. Findings will be used to inform future research efforts of the USDA Germplasm Enhancement of Maize project and eventually aid in the rapid adaptation of exotic germplasm to temperate U.S. environments.